Kedudukan Anak Angkat dalam Hak Waris pada Masyarakat Islam di Kota Palopo (Relevansinya pada Pengadilan Agama Palopo) - Amir, Rahma (LP2M IAIN Palopo, 2016)
According to the law, Islamic Law Compilation (KHI) is a written law that used as specific guidelines for Muslims in resolving all legal issues including on the status of an adopted child. Therefore, this study aims to: 1). Knowing the position of adopted children with KHI and Civil Law, 2). Knowing the position of adopted children and their legacy rights. 3). Knowing the position adopted child and the adoptive parents, their legacy and guardian of the marriage.Keywords: Adopted Child, Legacy Rights, Religious Court